Komitmen Organisasi Sebagai Mediator Antara Kepemimpinan Transformasional dan Organizational Citizenship Behavior Terhadap Kinerja Karyawan - I Nyoman Sudirga Yusa; Fathorrahman Fathorrahman; Tin Agustina K (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2026)
This study evaluates the influence of transformational leadership and organizational citizenship behavior (OCB) on employee performance, with organizational commitment as an intermediary variable. The study was conducted at PT Pramana Manajemen Internasional, a hotel management company. The study employed a quantitative approach and census technique involving all employees as respondents. Data analysis was conducted using Structural Equation Modeling using SmartPLS 4.0 software. The results indicate that both transformational leadership and OCB have a positive and significant influence on organizational commitment and employee performance. Furthermore, organizational commitment was shown to significantly link the two independent variables to performance. These findings contribute to the understanding of leadership theory and organizational behavior and offer practical recommendations for improving human resource performance.